SYNTAX and Coronary Artery Calcium Score Predict Atherosclerotic Plaque Formation in the Ascending Aorta - Haberal, Ismail; Balli, Mehmet; Tekin, Esra Erturk; Uysal, Ayhan; Ozsoy, Sadiye Deniz; Yesiltas, Mehmet Ali; Aydinli, Bahar (Forum Multimedia Publishing, Llc, 2021)
Background: There is no study about the relationship between the complexity of coronary artery disease (SYNTAX SCORE; SS), and coronary artery calcium (CAC) score, accom-panied with aortic calcium score (ACS) levels. The objective of this study was to investigate the relationship between the pre-operative SS and CAC scores accompanying ACS in isolated CABG patients and their postoperative clinical results. Methods: This study included 130 consecutive CABG patients. The mean age of the patients was 62.3 +/- 8.62 years (range: 47-84 years). SS was measured using coronary angi-ography by an experienced cardiologist. We investigated the ACS accompanied with CAC scores using a multidetector computed tomography (MDCT) in the same session, pre-operatively. Measurements of the CAC score and ACS were measured by an experienced radiologist, who was unaware of the study in the same session. In order to investigate aortic wall pathology in patients with positive aortic calcification, we provided aortic tissue samples prior to the proximal anas-tomosis of bypass grafts using No:11 scalpel. Results: Overall median SS was 39 +/- 7.2 (range: 15-41). CAC score was zero in 34 patients (26.1%). For the patients with a CAC score of zero, the median SS was 32 +/- 9.4. There was no evidence of aortic calcification or plaque formation in 62 patients (47.6%). In these patients, the median SS was 35.6 +/- 11.3. No significant difference was found when both groups were compared and for those patients with a calcific score of zero (P = .85). The median CAC score and ACS were 238 +/- 122 AU (range: 0-1238 AU) and 112 +/- 40 AU (range: 0-730 AU), respectively (P = .0033). For patients with a CAC score and ACS >_400 AU, the mean SYNTAX score was >_ 37. SS was correlated with CAC score (R:0.585; P < .0001). SYNTAX was correlated with ACS (R:0.557; P < .001). In multivariate analysis of SS (OR 1.053, 95% CI: 1.003-1.106, P = .039), gender (OR 0.189, 95% CI: 0.053-0.678, P = 0.011), age (OR 1.454, 95% CI: 1.256-1.632, P = .012), and diabetes mellitus (OR 0.341, 95% CI: 1.006-1.124, P = .014) were independent predictors for CAC score and aortic calcification. Conclusions: CAC score and ACS are strongly correlated with the complexity of coronary arteries in CABG patients. The total CAC score (>_ 400 AU) was independently associ-ated with the degree of SS (>37). To prevent MACCE and mortality in CABG patients, we suggest the measurement of CAC score accompanied with ACS using MDCT as a non-invasive method. Highlight points: center dot Atherosclerotic plaque formation in aorta and coro-nary arteries are the main risk factors for stroke and infarction in CABG operations. center dot SYNTAX score value and aortic atherosclerosis levels are directly correlated. center dot SYNTAX score may predict the complications due to atherosclerosis during heart surgery.
Keywords: Disease; Mortality; Surgery; Burden; Risk